2008
DOI: 10.1074/jbc.m800608200
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycans and the N Terminus of Protein C Inhibitor Affect the Cofactor-enhanced Rates of Thrombin Inhibition

Abstract: Protein C inhibitor (PCI) is a serine protease inhibitor, displaying broad protease specificity, found in blood and other tissues. In blood, it is capable of inhibiting both procoagulant and anticoagulant proteases. Mechanisms that provide specificity to PCI remain largely unrevealed. In this study we have for the first time provided a full explanation for the marked size heterogeneity of blood-derived PCI and identified functional differences between naturally occurring PCI variants. The heterogeneity was cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 41 publications
1
34
1
Order By: Relevance
“…Multiply fucosylated N-glycans were detected in seminal plasma (44). One of the proteins extensively fucosylated in seminal plasma is protein-C inhibitor, but this protein in plasma carries Nglycans with at most two fucoses (45,46). Zona pellucida and sperm N-glycans with extensive fucosylation were described to modify protein interactions in the reproductive context, although a recent report described hyper-fucosylated lactosamines with up to six fucoses on N-linked glycans in pancreatic cyst fluids primarily associated with ␣-amylase and triacylglycerol lipase (47,48).…”
Section: Glycosylation Of Hp In Cancer Andmentioning
confidence: 99%
“…Multiply fucosylated N-glycans were detected in seminal plasma (44). One of the proteins extensively fucosylated in seminal plasma is protein-C inhibitor, but this protein in plasma carries Nglycans with at most two fucoses (45,46). Zona pellucida and sperm N-glycans with extensive fucosylation were described to modify protein interactions in the reproductive context, although a recent report described hyper-fucosylated lactosamines with up to six fucoses on N-linked glycans in pancreatic cyst fluids primarily associated with ␣-amylase and triacylglycerol lipase (47,48).…”
Section: Glycosylation Of Hp In Cancer Andmentioning
confidence: 99%
“…Plasma PCI has three N-glycosylation sites at Asn-230, Asn-243 and Asn-319 [13], [14]. We and other groups have observed that the N-glycans of PCI affect the rates of inhibition of several proteases [14], [15].…”
Section: Introductionmentioning
confidence: 92%
“…Results for human plasma samples spiked with 0.1-1 U/mL rVWF (Table 2) confirmed the adequate precision of the procedure with RSDs of less than 10%. Mean recovery of spiked rVWF was acceptable for the samples containing 1 and 0.5 U rVWF with mean recoveries of 85.1% [1]- [3] show the results for three independent runs in sample aliquots, n.a. = not applicable.…”
Section: Measurement Of Rvwf In Macaque and Human Plasma With The Depmentioning
confidence: 99%
“…It supports proper folding, enables targeting of protein and ligand binding, modulates biological activity, contributes to stability and determines circulatory serum half-lives [1][2][3][4][5]. The carbohydrate to the protein linkage allows differentiation between different classes.…”
Section: Introductionmentioning
confidence: 99%